China entering the Xi Jinping era - Yongnian, Zheng; Gore, Lance, 1958- (London : Routledge, 2014)
'How will China develop under the new leadership of Xi Jinping and Li Keqiang? This is a key question for both China and the wider world. This book presents a comprehensive overview of the key areas and issues within China, assessing how things are likely to develop under the new leadership. The book emphasises the great uncertainty surrounding the next phase of China's development, highlighting deep social divisions over issues such as income disparity, rampant corruption and unequal opportunities, and arguing that the political purge of Bo Xilai has not been resolved, with many of the polices and rhetoric of the discredited Bo Xilai model continuing to exert a strong influence'--
Includes bibliographical references and index.
Keywords: Xi, Jinping; Political leadership -- China; China -- Politics and government -- 2002-; China -- Social conditions -- 2000-; China -- Social policy; China -- Foreign relations -- 21st century